Food for thought: progress in understanding the causes and mechanisms of food allergy. Issue 3 (June 2015) - Ashley, Sarah; Dang, Thanh; Koplin, Jennifer; Martino, David; Prescott, Susan
Abstract : Purpose of review: The community burden of food allergy appears to be rising, yet the causes and mechanisms are not completely understood. The purpose of this review is to provide a snapshot of the state of play of IgE food allergies, with a focus on recent advances. Recent findings: There are still wide discrepancies regarding measures and definitions of food allergy. Even recent studies still rely on food sensitization, self-reporting, or parent-reporting rather than more robust measures. Population-based sampling strategies using objective measures are underway in some countries. Emerging data suggest substantial geographical and ethnic differences in food sensitization and allergy. Trans-cutaneous sensitization, particularly in those with eczema or filaggrin mutations, has been posited as a potential mechanism, as well as gut microbiota and genetics/epigenetics. Treatments for food allergy are still lacking, yet progress is being made, and immunotherapy appears more effective than dietary avoidance. Non-IgE food allergy remains drastically under-explored. Summary: Food allergy is a complex immune-mediated disease consisting of numerous environmental/genetic/epigenetic risk factors; yet interventions are likely to be simple and cost-effective.